CORRELATION BETWEEN RED BLOOD CELL DISTRIBUTION WIDTH AND B-TYPE NATRIURETIC PEPTIDE (BNP) IN PATIENTS WITH ACUTE CORONARY SYNDROME - RAMEEJAN BEGUM,; REVATHI SHREE, (International Journal of Pharma and Bio Sciences, 2016)
This study was undertaken to determine the correlation between brain natriuretic peptide (BNP) and red cell distribution width (RDW) in the acute coronary syndrome. It was done on hundred adult patients who were diagnosed with acute coronary syndrome and hospitalized in the Coronary care unit in Chettinad Hospital Research and Institute (CHRI), Kelambakkam. Patients were selected based on the inclusion criteria. ST-segment elevation and ST-segment depression proven by electrocardiography. Acute failure shows an ejection fraction less than 50% proven by echocardiography Serum BNP levels > 400 pg/mL Complete blood count and biochemical markers which include BNP, Troponin I, CPKMB were used for analyses within less than 24 hours of admission. The correlation between the three outcome variables and the explanatory variables was assessed by calculating correlation coefficients and its P-value and 95% CI. The study observations are as follows: The mean age was older and there were more males in the ACS study group. RDW showed statistically significant positive correlation with BNP levels (correlation coefficient 0.147, p value <0.001) There was a weak positive correlation between Total leucocytes count and BNP levels (Correlation coefficient 0.013) and it was statistically not significant (P value 0.267). To conclude, Elevated RDW levels is independently associated with a higher BNP level in patients with acute coronary syndrome. RDW has been proven to be as good as BNP.